The Destruction of Antiquity in Syria and Iraq - We Ought to Care About a Viable Solution - Engele, Meghan; Desmit, Jenna; Tariq, Aqsa (MacEwan University Student eJournal, 2015)
Syria and Iraq are home to numerous ancient civilizations which have been instrumental in helping modern humans understand the dawn of civilization. While human casualties are often the media focus, the permanent loss of historic sites and artifacts is a long term economic burden for local communities that rely on tourism, and the global cultural heritage within Syria and Iraq simply cannot be replaced once it is gone. This paper will explore the fundamentalist ideals which fuel the desecration of antiquity, the historic relevance of variety of damaged or destroyed sites, and we will argue that a long term solution involves targeting the illegal trade of antiquities, the economic foundation of ISIS, and the withdrawal of aggressive foreign military forces.